Quality Assessment of Buffalo Milk Chakka Prepared from Different Starter Culture : Quality Assessment of Buffalo Milk Chakka ............... - Vihan, Varsha; Umaraw, Pramila; Singh, V. P.; Verma , Akhilesh K.; Singh, Chirag; Verma , Shardanand (Indian Journal of Dairy Science, 2023)
Chakka is a soured dairy product that is produced by removing the whey from fermented milk (dahi, known as Indian yogurt). The starter culture plays a significant role in determining the overall elemental quality of fermented dairy products. The present study was carried to find out the suitability of three different cultures for development of chakka viz. T1 (1.5% Mixed microbial culture), T2 (1.5% bacterial culture (STI-13 freeze-dried Lactic culture)), and T3 (1.5% yeast cultures). Among the different culture various quality characteristics, physico-chemical parameters and sensory characteristics were assessed for their ability to form chakka. Curd prepared from the lactobacillus culture (T2) was found most suitable for preparation of chakka as T2 delivered highest yield of curd mass, protein, least pH value and moisture content compared to microbial culture and yeast culture. Sensory attributes of chakka also varied significantly (P≤0.05) among cultures. All sensory attributes rated higher for T2 (lactobacillus cultures). Therefore, result of the study concluded that T2 (1.5% lactobacillus) culture was most appropriate for formulation of chakka.